Synthesis of optimal filter course in channel navigation system - Блохін, Л.М.; Літвинова A.I.; Корновський, Р.Р.; Півень, М.А. (Proceedings of National Aviation University, 2006)
Algorithms and results of choice of optimum structure of filter in the canal of the real navigation system’s course for its modernization were presented. Data of dynamic testing of the canal of course of navigation system were used during the process of synthesis.